Thomas Nisbet: A Reappraisal of His Life and Work - Dilworth, T. G. (Material Culture Review, 1982)
The life and craft history of Thomas Nisbet (1777-1850) is given here; his work is related to that of other New Brunswick cabinet-makers of the period and the problems of accurate attribution are discussed. Résumé Cette communication donne un compte rendu de la vie de Thomas Nisbet et de son évolution comme artisan (1777-1850), en situant sa production par rapport à celle d’autres ébénistes du Nouveau-Brunswick à la même époque et en examinant les problèmes d’attribution.